Music on Dutch Moroccan websites. (1st January 2013) - Merolla, Daniela
Music is present online and offline alike, only amplified in volume and diffusion by the increase in audio and visual technology. However, music is controversial as well, when we consider current and long-term debates over acceptance and rejection of music in Islam. Looking at music as both social practice and artistic product, this article investigates its presence on websites created by Dutch Moroccans in the Netherlands and explores the way in which Internet-mediated music contributes to characterizing such sites. Five websites are investigated: El Tawheed, which is presented by other sites as the site of a 'Moroccan mosque', Ontdekt Islam/Discover Islam, Maroc.nl, which is a popular website, and two Berber websites, Amazigh.nl and Tawiza.nl. The analysis ties in with results and insights of a rich amount of works that have addressed websites variously indicated as 'Muslim', 'allochthonous', 'ethnic', 'minority' and 'migrant'.1 Studies by J. W. Anderson, A. Appadurai and D. Miller and D. Slater have been source of inspiration. Finally, this article discusses the adequacy of the religion/secularism opposition in understanding ideas and prac¬tices of music as expressed by Dutch Moroccan websites.